Presence of Anti-Interferon Antibodies is Not Associated with Non-Response to Pegylated Interferon Treatment in Chronic Hepatitis B. Issue 4 (May 2014) - Arends, Pauline; van der Eijk, Annemiek A; Sonneveld, Milan J; Hansen, Bettina E; Janssen, Harry LA; Haagmans, Bart L
Background: Several factors have been related to response to pegylated interferon (PEG-IFN) in chronic hepatitis B (CHB). The occurrence of anti-IFN antibodies is associated with non-response to PEG-IFN in chronic hepatitis C. This study investigated the association between anti-IFN antibodies and response to PEG-IFN in CHB. Methods: Presence of anti-IFN antibodies was assessed at baseline and at 3 and 6 months post-treatment in 323 CHB patients treated with PEG-IFN for 1 year. Results: At baseline, anti-IFN antibodies were detected in 112 (35%) patients. Prevalence was higher in HBeAg-negative compared to HBeAg-positive CHB (43% versus 31%, respectively; P =0.03). Detection of anti-IFN antibodies was not associated with age, sex or HBV genotype. Presence of anti-IFN antibodies at baseline was associated with previous IFN therapy failure ( P =0.04), which remained after adjustment for HBeAg status (OR 2.0, 95% CI 1.1, 3.7; P =0.03). Presence of anti-IFN antibodies at baseline was not associated with response, nor with HBV DNA or HBsAg decline (all P -values >0.3). Overall, 56 of 211 (27%) patients without anti-IFN at baseline developed anti-IFN antibodies after PEG-IFN treatment. Response rates did not differ between patients who developed anti-IFN antibodies and patients who did not develop anti-IFN antibodies during treatment ( P =0.1). Conclusions: Anti-IFN antibodies may frequently be detected in CHB patients, and presence is associated with previous IFN therapy. However, presence or development of anti-IFN antibodies after PEG-IFN therapy is not associated with non-response to PEG-IFN treatment in CHB. There appears to be no future role for anti-IFN antibodies in predicting response to PEG-IFN in CHB.